A identidade étnica indígena no discurso político do movimento zapatista: a voz do "Viejo Antonio" (1994-1998) - Vitali, Marcela Araújo (2014)
The EZLN or Zapatista Army of national liberation emerged in the Mexican scenery from 1994, and became a social movement organized around the indigenous ethnic identities of the state of Chiapas. Since their public appearance, the zapatistas communicated with civil society and their sympathizers through bulletins, letters, tales and stories that were published in newspapers, internet, and other means of communication. The main discursive voices of the movement are represented by the CCRI-CG (clandestine revolutionary indigenous Committee-General Commanding) and by the assistant commandant Marcos (one of the spokeman of the movement). Our research has examined the tales written by Marcos, in which its main protagonist was ViejoAntonio, a character who reports the mythic, political and social aspects of the world of indigenous Mayan origin. In addition, it was interesting to understand this discursive production as an expression of the zapatista indigenous ethnicity, taking into consideration their production processes and enunciation and operacionalization of the -diacritics signals of the ethnic identity? in interrelation contexts of these people with the State and with Mexican civil society. Our documentary analysis has opted for the tales and stories published between the years of 1994 and 1998.